El Laboratorio de Entomología Médica de Florida - Jorge R. Rey; C. Roxanne Rutledge Connelly; Chelsea T. Smartt (EDIS)
ENY744S, a 6-page illustrated fact sheet by Jorge R. Rey, C. Roxanne Connelly, and Chelsea T. Smartt, is the Spanish language version of ENY-744/IN772: The Florida Medical Entomology Laboratory. It describes this UF/IFAS facility located in Vero Beach FL, and its research, education, and teaching programs. Published by the UF Department of Entomology and Nematology, November 2009.